Management of Instagram @kantahkabbogor1 as a Media for Information and Publication - Qothrunnada, Adinda; Bachtiar, Willy (Journal of Communication Studies, 2025)
The development of social media has played an important role in public communication of government agencies, including in conveying land service information to the public. This research aims to find out how the management of Instagram @kantahkabbogor1 is carried out by the Public Relations of the Bogor Regency Land Office I as an information and publication medium, as well as the obstacles faced in its implementation. This study uses a qualitative approach through observation, interviews, active participation, and literature studies by referring to The Circular Model of SoMe consisting of the Share, Optimize, Manage, and Engage stages as an analysis framework. Research results show that Public Relations has played a role in Instagram as a medium for disseminating land information through visual content that is informative and easy to understand by the public, as well as structured management strategies. The management still faces several obstacles such as human resource limitations, internal coordination that takes longer, and limitations of available devices. Public Relations of the Bogor Regency Land Office I are still able to maintain the sustainability of publications and support the transparency of public information through adaptive social media management strategies despite obstacles.